14.1k views
0 votes
Given: f(x) 3x-1. g(x) 2x^2-3

=(3x-1) + (2x^2-3)
= 3x-1 + 2x^2-3
=5x^2-4

can someone tell me if its correct, im not sure if i am ;-;​

2 Answers

2 votes

Answer:


2x^(2) + 3x - 4

Step-by-step explanation:

(f + g)(x)=(3x-1)+(2x^2-3)

Simplify:

2x^2+3x−4

User Shivam Mitra
by
5.1k points
3 votes

Solution:

f(x) = 3x - 1 = 0

f(x) = x = 1/3

By putting the value of x in g(x), we get

g(x) = 2(1/3)^2 - 3

g(x) = 2(1/9) - 3

g(x) = 2/9 - 3

g(x) = -25/9

Answer:

g(x) = -25/9

User MoustafaAAtta
by
4.9k points